Challenges and perspectives on consolidation of Graduation Program in Design at UFMA: a look at the last quadrennium - Noronha, Raquel Gomes; Diniz, Raimundo Lopes; Santos, Denilson Moreira (DAT Journal, 2021)
This paper contextualizes the Graduate Program in Design at the Feder-al University of Maranhão (PPGDg-UFMA) in the city of São Luís, Maranhão, and presents, in a historical perspective, the changes around the lines of research in line with the faculty and the impacts on student education, encompassing the description of the quadrennium activities between 2017 and 2020. Institutional initiatives and actions for its maintenance and qualification as a graduate program are discussed, following the new CAPES guidelines. From the partnerships at the local and national level, over the years, a vision and positioning of a program that impacts socially and culturally its surroundings emerges and, through the strengthening of the teaching, research and extension tripod, it is articulated in favor of sustainable and interdisciplinary ways of doing and thinking about design at the graduate level. Finally, it brings the debate on the implications and challenges for the qualification and consolidation of a program located in the Legal Amazon, considering the regional, historical and technological characteristics.